Navigation Methods in Multiobjective Optimization - Nieminen, Matias Einopekka (2024)
Multiobjective optimization is the minimization or maximization of multiple conflicting objective functions. To make a distinction between multiple solutions to a multiobjective optimization problem, often a decision maker (DM), a domain expert, is needed to provide their preferences. Navigation methods for multiobjective optimization generate and visualize solutions in real-time, and allow a DM to control the solution process by changing their preferences during the process. In this thesis, a literature review was conducted to establish an understanding of the state of the art in navigation methods for multiobjective optimization problems. Based on the results of the review, a synthesis was formed to find out what kind of navigation methods exist, what features they have, and what, if anything, they have in common. The found navigation methods were analyzed and compared in terms of the type of solutions (i.e., Pareto optimal or approximated solutions) the DM sees during the solution process, whether and how they fulfill the desirable properties for navigation methods, defined in the literature. Some common features related to the implementations of the methods and their graphical user interfaces were found. Based on the synthesis, one can learn about the methods, and the synthesis may aid the DM in choosing a method when solving a multiobjective optimization problem. One may also develop a new optimization method by combining the different features of the methods found in the synthesis.